Analysis of the possible contribution of different nuclear fusion technologies to the global energy transition - D. Lerede; M. Nicoli; L. Savoldi; A. Trotta (Energy Strategy Reviews, 2023)
Despite the huge uncertainties related to the possibility of a quick development of nuclear fusion technologies - being disputed that it may come too late to effectively contribute to emission mitigation - research is focusing on a wide set of options for fusion reactors. This paper presents a global scenario analysis using the energy system optimization model EUROfusion TIMES to analyze the possible future role of fusion according to three different technologies and using capacity curves based on historical trends for the electricity sector. The analyzed fusion options are based on ARC, EU-DEMO and Asian-DEMO reactor concepts, characterized in terms of techno-economic features according to publicly available literature and considering a set of educated growth rate for their penetration. Results concerning installed capacity trends and contribution to the electricity mix are presented up to 2100 in three socio-economic storylines and for different scenarios considering either the availability of competing technologies or delays in the development of fusion plants. Despite not contributing at all to the energy transition in Europe and the US, fusion may gain share in contexts characterized by highly growing electricity demand, contributing to satisfy stringent environmental constraints together with other low-carbon technologies in the second half of the century.